Peñalba, A. & Santiago, R. B. (2020). Técnicas de musicoterapia para logopedas. Editorial Síntesis - Luis del Barrio Aranda (Ediciones Complutense, 2022)
Reseña de la obra de Peñalba, A. & Santiago, R. B. (2020). Técnicas de musicoterapia para logopedas. Editorial Síntesis